Investigation of a Time-Dependent Source Identification Inverse Problem with Integral Overdetermination. (3rd October 2017) - Ashyralyev, Allaberen; Sazaklioglu, Ali Ugur
ABSTRACT: In the present paper, a time-dependent source identification problem subject to an integral overdetermination is considered. Stability estimates for this differential problem are established. Furthermore, a first and a second order of accuracy difference schemes are proposed for the approximate solution of this problem. Stability and almost coercive stability estimates for these difference schemes are established. Additionally, some illustrative numerical results are provided.